2022
DOI: 10.3389/fimmu.2021.737747
|View full text |Cite
|
Sign up to set email alerts
|

Autoinflammatory Keratinization Disease With Hepatitis and Autism Reveals Roles for JAK1 Kinase Hyperactivity in Autoinflammation

Abstract: Heterozygous mutations in JAK1 which result in JAK-STAT hyperactivity have been implicated in an autosomal dominant disorder that features multi-organ immune dysregulation. This study identifies another previously unreported heterozygous missense JAK1 mutation, H596D, in an individual with a unique autoinflammatory keratinization disease associated with early-onset liver dysfunction and autism. Using CRISPR-Cas9 gene targeting, we generated mice with an identical Jak1 knock-in missense mutation (Jak1H595D/+;I5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…JAK inhibitors have already been approved as human AD drugs, and many JAK inhibitors have advanced to clinical studies ( 44 ). Two reports have indicated that increased Jak1 activity led to an inflammatory skin phenotype in mice ( 45 , 46 ). Therefore, it is suggested that Jak1 is important for maintaining skin homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…JAK inhibitors have already been approved as human AD drugs, and many JAK inhibitors have advanced to clinical studies ( 44 ). Two reports have indicated that increased Jak1 activity led to an inflammatory skin phenotype in mice ( 45 , 46 ). Therefore, it is suggested that Jak1 is important for maintaining skin homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…[17] In the brain of mice with 22q11.2 deletion syndrome, activation of JAK1 leads to auto-inflammation and may cause neurological dysfunction. [18] 2.1.2. The function of JAK2.…”
Section: The Function Of Jak1mentioning
confidence: 99%
“…JAK1 -activating mutations were detected in hematologic malignancies, such as acute lymphoblastic leukemia [ 91 ]. Based on a recent report, heterozygous JAK1 mutations were also implicated in triggering superficial cutaneous inflammation and aberrant keratosis [ 92 ].…”
Section: Autoinflammatory Keratinization Diseasesmentioning
confidence: 99%
“…Recently, a case report of a child with early-onset ichthyotic eczema coexisting with eosinophilia, liver abnormalities, growth retardation, and autism was published [ 92 ]. Quickly progressing hepatic cirrhosis produced the necessity to perform liver transplantation at the age of 3 years.…”
Section: Clinical Approach To Autoinflammatory Keratinization Diseasesmentioning
confidence: 99%